2020
DOI: 10.1002/adfm.202003683
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Gated MoS2 Memtransistor Crossbar Array

Abstract: Memristive systems offer biomimetic functions that are being actively explored for energy-efficient neuromorphic circuits. In addition to providing ultimate geometric scaling limits, 2D semiconductors enable unique gatetunable responses including the recent realization of hybrid memristor and transistor devices known as memtransistors. In particular, monolayer MoS 2 memtransistors exhibit nonvolatile memristive switching where the resistance of each state is modulated by a gate terminal. Here, further control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 71 publications
2
114
0
Order By: Relevance
“…This is the typical behaviour of an electronic synapse, where the decreasing of conductance is attributed to potentiation, while the conductance increase is attributed to synapse depression [21,22]. A comparison of our results with similar results obtained for a dual-gate memtransistor having MoS 2 as channel instead of graphene monolayer [8] is presented in Table 2. The parameters taken into account are the maximum drain current, I D,max , the maximum voltage values for the top and back gates, V TG,max and V BG,max , the maximum drain voltage, V D,max , the on-off ratio, and the memory window.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This is the typical behaviour of an electronic synapse, where the decreasing of conductance is attributed to potentiation, while the conductance increase is attributed to synapse depression [21,22]. A comparison of our results with similar results obtained for a dual-gate memtransistor having MoS 2 as channel instead of graphene monolayer [8] is presented in Table 2. The parameters taken into account are the maximum drain current, I D,max , the maximum voltage values for the top and back gates, V TG,max and V BG,max , the maximum drain voltage, V D,max , the on-off ratio, and the memory window.…”
Section: Resultssupporting
confidence: 79%
“…This drain voltage value can decrease by up to 12 V by introducing top gate configurations [6] or using localized beam irradiation techniques [7]. Additionally, recent crossbar arrays of MoS 2 memtransistors incorporating an array of 10 × 10 FETs [8,9] have been reported, paving the way for memtransistor applications in resistive memories and neuromorphic computation.…”
Section: Introductionmentioning
confidence: 99%
“…However, refs. [ 6–10 ] used high temperatures (≈800 °C) during the fabrication of the devices, which is not compatible with back‐end‐of‐line (BEOL) processes, as these do not permit temperatures >450 °C. [ 11,12 ] Furthermore, in all the aforementioned studies the current flows horizontally along the 2D‐LM (i.e., in‐plane), and it has been demonstrated that grain boundaries (GB), [ 13 ] wrinkles, [ 14 ] and polymer residues [ 15 ] can remarkably alter the properties of the devices in an uncontrollable way.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the hysterical effect has been found in a multitude of materials, such as PCM, twodimensional materials 22,27 , perovskite 28,29 . By integrating these materials into the metadevices, the SLM capable of multi-state storage is extendable to a broad frequency range from microwave to visible light.…”
Section: Discussionmentioning
confidence: 99%